Analisis Pengaruh Iklan di Sosial Media dan Penggunaan Selebritas Terhadap Minat Beli Produk Melalui Kesadaran Merek Sebagai Variable Intervening pada Produk Bloods - Aditya, Rizky; Susila , Ihwan (Masyarakat Ekonomi Syariah Bogor, 2024)
The main purpose of this study was to examine the effect of social media advertising,celebrity use and brand awareness on interest in buying Bloods products, especially in Bloods consumers. The research method used is quantitative method, and the sample amounted to 183 respondents social media users/consumers bloods and using purposive sampling. Reliability and validity of questionnaires were assessed in various circles. Data were analyzed using partial least square (PLS) technique with SmartPls 3.0 application. The findings show that social media advertising, celebrity use and brand awareness have a significant effect on interest in buying Bloods products.